PENGARUH PEMBERIAN EKSTRAK RUMPUT KEBAR (Biophytum petersianum Klotzsch) TERHADAP JUMLAH SEL SERTOLI MENCIT (Mus musculus) YANG DIPAPAR 2,3,7,8-TETRACHLORODIBENZO-P-DIOXIN - Berlina, Cyrcilia Relita; Eliyani, Hana; Sami, Abdul; Widjiati, Widjiati; Mulyati, Sri; Anwar, Chairul (Journal of Basic Medical Veterinary, 2019)
This study  was aimed  to know  the effect of Kebar grass  extract  on amount of mice  Sertoli  cell exposed  by TCDD.  This study was  experimental   study  with completely   randomized  design.  Thirty adult  male  mice  of Mus  musculus strain Balb/C,  age 11 weeks  and  weight   25 - 30 ~were    used.  Mice were divided   into five groups,   that  were:  K- was  control  (aquadest   0)   mL); K+ was  injected  with TCDD  at  dose  of 7 µg/kg   BW;  Pl  was  injected  with TCCD  and  administrated with   Kebar   extract   (0,045 mg/  g  BW/day);   P2 was   injected   with   TCCD  and administrated  with  Kebar  extract  (0,080 mg/ g BW/day);   P3 was  injected  with TCDD and  administrated with  Kebar extract  (0,135 mg/  g BW/day).   Kebar grass extract  was  administrated in 53 days.  Mice were sacrificed  and  right  testis organs were  taken.  Then, histology   preparat  with  HE  staining   were  made  and  Sertoli cells  were  counted.    Data were   analyzed  by  One  Way  ANOV A  followed   by Duncan test  (a  =  0,05).   The result  of this  study   showed that  administration  of Kebar  grass  extract  affected  amount  of mice sertoli  cells.  K+ (2,92a±0,109) showed significance difference  (p<0,05) compared   to Pl (5,00b±0,374), P2 (7,64c±0,409)  and P3 (9,68ct±0,363).  Meanwhile, amount   of Sertoli cells of P3 at the highest  dose  did not  show  significance difference   (p>0,05)  with  K-  (10,16<l±0,829).  The conclusion of this study was  administration of Kebar  grass  extract  per  oral in 53 days  could maintain amount  of mice Sertoli cell exposed  by TCDD.